Unusual Occurrence of Rare Lipid-Rich Carcinoma and Conventional Invasive Ductal Carcinoma in the One Breast: Case Report - Katarina Machalekova; Karol Kajo; Marian Bencat (Hindawi Limited, 2012)
A 56-year-old woman noticed a palpable mass in her left breast during self-examination. Patient was admitted to our hospital and malignant bifocal tumour was diagnosed by ultrasonography, digital mammography, magnetic resonance, and core-cut biopsy. The patient underwent planned conservative surgery (biquadrantectomy) with a sentinel node examination, but after results of the frozen section with positive resection margins and positive sentinel lymph nodes subsequent mastectomy with axillary lymph node dissection were realized. Histology in the resection specimen revealed two isolated and distinct tumours. One of the lesions represented conventional invasive ductal carcinoma of histological grade 3, and the second tumour was evaluated as invasive lipid-rich carcinoma, containing tumour cells with clear and foamy cytoplasm. Lipids in neoplastic cells were detected by Oil Red O staining and ultrastructural examination. Immunohistochemical analysis of both carcinomas was almost identical with negative steroid receptors, positive staining of HER-2, and p53 and with high proliferation activity (Ki-67). Mastectomy specimen contained residual foci of invasive ductal carcinoma and dissected axillary lymph nodes were free of metastasis. Patient underwent first cycles of chemotherapy with paclitaxel and Herceptin together with local radiotherapy and two month after surgery is without any evidence of the disease.